PILIHAN KODE DALAM INTERAKSI BELAJAR-MENGAJAR DI PESANTREN (KAJIAN SOSIOLINGUISTIK) - Eka Susylowati (TELAGA BAHASA, 2020)
The diversity of languages used by santri (student) community can represent the existence of multi-ethnic and multilingual communities. The purpose of this study is to reveal the language choice in teaching and learning interactions between students and students with teachers in Al-Mukmin Ngruki Islamic Boarding School and Assalaam Modern Islamic Boarding School. This research is a qualitative descriptive study using the Sociolinguistics approach. Data collected used the method of observation, recording, and interviews. The data in this study was in the form of student speech in an Islamic boarding school. The data were analyzed using the Hymes ethnography communication method. The results of this study indicate that there are variations in the codes used by students, namely Indonesian, foreign languages, Javanese, and mixed languages in the form of code-switching and code-mixing from Javanese to Indonesian, and Javanese to English.